1998
DOI: 10.3141/1643-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-Term Pavement Performance Plan Wall Projection-Based Distress Data Variability

Abstract: In the Long-Term Pavement Performance (LTPP) program, 35-mm, black and white, continuous-strip photographs are used as a permanent record of pavement distress development for archival purposes and to quantify the distress severity and extent for pavement performance analysis. The traditional method of interpreting distress from LTPP film utilizes a relatively small image projected onto a digitizing tablet. From quality control checks performed on the interpreted data, it was found that some low severity types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recognizing that the LTPP program distress raters are experienced individuals, such improvements are not envisioned to come through additional training and they contend that the only way to achieve the desired improvement is to conduct group consensus surveys. Shekharan et al (1998) also showed that the overall variability of manual distress data is lower than for that from film interpretations. Furthermore, the bias (average difference between manual and film interpretations on the same sections) was much higher for the film interpretation than for the manual surveys.…”
Section: Quality Management In Automated Pavement Data Collectionmentioning
confidence: 93%
“…Recognizing that the LTPP program distress raters are experienced individuals, such improvements are not envisioned to come through additional training and they contend that the only way to achieve the desired improvement is to conduct group consensus surveys. Shekharan et al (1998) also showed that the overall variability of manual distress data is lower than for that from film interpretations. Furthermore, the bias (average difference between manual and film interpretations on the same sections) was much higher for the film interpretation than for the manual surveys.…”
Section: Quality Management In Automated Pavement Data Collectionmentioning
confidence: 93%
“…• LTPP Distress Variability Study (4,(7)(8)(9)(10). The objectives of this study were to assess the variability of manual and film-derived distress data collected for the LTPP program and to quantify the bias and precision of those distress data.…”
Section: Other Qc-qa Elementsmentioning
confidence: 99%
“…Thus, the frequency of distress data collection could add to the uncertainty in performance prediction (2). Uncertainty associated with the method of condition data collection (manual, semiautomated, and automated) has been well documented in the literature (ASTM STP 1121; [3][4][5][6][7][8][9][10][11][12][13][14]. However, an investigation of the effects of condition monitoring frequency on pavement management decision on highway maintenance, rehabilitation, and reconstruction is needed.…”
mentioning
confidence: 99%